E-Point Septal Separation as a Surrogate Marker for Global Longitudinal Strain in Predicting MACE after ST Elevation Myocardial Infarction - Sarahazti, Mustika Fadhilah; Hasan, Harris; Ketaren, Andre Pasha (Indonesian Journal of Cardiology, 2018)
Background: Global Longitudinal Strain (GLS) is a sensitive measurement and has been studied as a parameter to assess myocardial deformity and had a prognostic value in STEMI patient, but this measurement is usually taken at echocardiography laboratory with software installed only, a simple parameter of systolic function that had been known is EPSS, the aim of this study is to determine the prognostic value of this simple parameter as a surrogate marker of myocardial deformity for mayor adverse cardiac event (MACE). Methods: This is an analytic observational study using ambispective cohort study, basic and echocardiographic data were collected from 66 adult subjects of acute STEMI from July 2016 until April 2017. Each subjects were followed-up for MACE (mortality, heart failure, ventricular arrhytmia and cardiogenic shock) 30 days since admission. Cut off point were taken from ROC curve. Statistical analysis test were used to examine the association between two variables and obtained odds ratio (OR) for EPSS. To obtain the degree of relationship between EPSS and GLS we were using corelation test with the value of p<0.05 was considered statistically significant. Result: In this study the optimum cut off value for EPSS was 7 mm with sensitivity and specificity of 72% and 71%, respectively. Bivariate analysis showed among EPSS >7 mm and GLS >-10,6% were associated with MACE in 30 days after STEMI. In multivariate analysis, GLS >-10,6% (OR 10,6 95%IK 2,5-44,7 p=0,001) and EPSS >7 mm (OR 5, 95%IK 1,12-22,56 p=0,035) remained significantly associated and had 83% probability for MACE in 30-days after STEMI. Using the corelation test we found that EPSS had a stronger relationship with GLS (r=0,795, p<0,001). Conclusion: Our data show that EPSS >7 mm had a strong relationship with myocardial deformity parameter and appears to be a strong predictor for MACE in 30-days after acute STEMI. Therefore, it can be taken earlier to help the cardiologist in emergency unit for futher appropriate management planning.   Abstrak Latar Belakang: Global Longitudinal Strain (GLS) adalah parameter deformitas miokardium yang telah banyak diteliti untuk menilai fungsi sistolik ventrikel kiri serta kaitannya terhadap prognosis pasien IMA-EST, sayangnya pemeriksaannya cenderung terbatas dilakukan di laboraturium ekokardiografi dengan alat ekokardiografi tertentu. Parameter fungsi sistolik lainnya yang cukup dikenal karena tekniknya yang sederhana dan dapat dilakukan di Unit Gawat Darurat adalah E-Point Septal Separation (EPSS), tujuan dari penelitian ini adalah melihat nilai prognosis EPSS sebagai indikator tidak langsung deformitas ventrikel kiri terdahap Kejadian Kardiovaskular Mayor (KKvM). Metode: Penelitian ini merupakan studi kohort ambispektif, 66 orang subjek IMAEST yang memenuhi kriteria inklusi dan eksklusi yang dirawat di Rumah Sakit Haji Adam Malik mulai Juli 2016 sampai April 2017 diambil data dasar dan ekokardiografinya, kemudian pasien diikuti selama 30 hari untuk KKvM (kematian, gagal jantung, aritmia ventrikel dan syok kardiogenik). Nilai titik potong EPSS diambil dari kurva ROC. Uji statistik dilakukan untuk menilai hubungan antara variabel untuk mendapatkan nilai rasio odds (RO) EPSS, uji korelasi digunakan untuk menilai kekuatan hubungan antara EPSS dengan GLS, p<0,05 dianggap bermakna. Hasil: Nilai titik potong EPSS yang didapatkan adalah 7 mm dengan sensitivitas 72%, spesifisitas 71%. Analisis bivariat menunjukkan nilai EPSS >7 mm dan GLS >-10,6% berhubungan dengan KKvM. Pada analisis multivariat, GLS >-10,6% (RO 10,6 95%IK 2,5-44,7 p=0,001) dan EPSS >7 mm (RO 5, 95%IK 1,12-22,56 p=0,035) secara signifikan tetap berhubungan dan memiliki probabilitas sebesar 83% dalam memprediksi KKvM 30 hari setelah IMAEST. Adapun nilai EPSS dan nilai GLS memiliki hubungan yang kuat (r=0,795, p<0,001). Kesimpulan: Data menunjukkan bahwa nilai EPSS >7 mm memiliki hubungan yang kuat dengan parameter deformitas ventrikel kiri dan suatu prediktor kuat pula terhadap KKvM dalam 30 hari setelah IMAEST. Hal ini menguntungkan kita sebagai klinisi karena dengan pemeriksaan EPSS yang sederhana ini dapat menjadi indikator adanya deformitas miokardium ventrikel kiri yang bernilai prognosis sehingga dapat dilakukan lebih dini untuk dapat menentukan strategi tatalaksana pada pasien IMAEST.